Systematic Review and Meta-Analysis on the Impact of COVID-19 Pandemic–Related Lifestyle on Myopia. Issue 5 (15th September 2022) - Li, Mijie; Xu, Lingqian; Tan, Chuen-Seng; Lanca, Carla; Foo, Li-Lian; Sabanayagam, Charumathi; Saw, Seang-Mei
Abstract : Purpose: To conduct a systematic review and meta-analysis to assess the effects of coronavirus disease 2019 (COVID-19) pandemic–related lifestyle on myopia outcomes in children to young adults. Methods: A systematic search was conducted on PubMed, Embase, and the Cochrane Central Register of Controlled Trials databases (with manual searching of reference lists of reviews). Studies included assessed changes in myopia-related outcomes (cycloplegic refraction) during COVID and pre-COVID. Of 367 articles identified, 7 (6 prospective cohorts; 1 repeated cross-sectional study) comprising 6327 participants aged 6 to 17 were included. Quality appraisals were performed with Joanna Briggs Institute Critical Appraisal Checklists. Pooled differences in annualized myopic shifts or mean spherical equivalent (SE) during COVID and pre-COVID were obtained from random-effects models. Results: In all 7 studies, SE moved toward a myopic direction during COVID (vs pre-COVID), where 5 reported significantly faster myopic shifts [difference in means of changes: −1.20 to −0.35 diopters per year, [D/y]; pooled estimate: −0.73 D/y; 95% confidence interval (CI): −0.96, −0.50; P <0.001], and 2 reported significantly more myopic SE (difference in means: −0.72 to −0.44 D/y; pooled estimate: −0.54 D/y; 95% CI: −0.80, −0.28; P <0.001). Three studies reported higher myopia (SE ≤−0.50 D) incidence (2.0- to 2.6-fold increase) during COVID versus pre-COVID. Of studies assessing lifestyle changes, all 4 reported lower time outdoors (pre-COVID vs during COVID: 1.1–1.8 vs 0.4–1.0 hours per day, [h/d]), and 3 reported higher screen time (pre-COVID vs during COVID: 0.7–2.8 vs 2.4–6.9 h/d). Conclusions: This review suggests more myopic SE shifts during COVID (vs pre-COVID) in participants aged 6 to 17. COVID-19 restrictions may have worsened SE shifts, and lifting of restrictions may lessen this effect. Evaluations of the long-term effects of the pandemic lifestyle on myopia onset and progression in large studies are warranted to confirm these findings.